The early church at work and worship. Volume 2, Catechesis, baptism, eschatology, and martyrdom - Ferguson, Everett, 1933- (Cambridge : James Clarke, 2014)
This is the second volume of Ferguson's collected essays, and includes some of his most memorable work.
10. Inscriptions and the Origin of Infant Baptism11. The Disgrace and the Glory: A Jewish Motif in Early Christianity; 12. The Kingdom of God in Early Patristic Literature; 13. Was Barnabas a Chiliast? An Example of Hellenistic Number Symbolism in Barnabas and Clement of Alexandria; 14. Millennial and Amillennial Expectations in Christian Eschatology: Ancient and Medieval Views; 15. Number Symbolism in the Ancient World; 16. Divine Pedagogy: Origen's Use of the Imagery of Education; 17. Early Christian Martyrdom and Civil Disobedience; Bibliography; Back cover.
Description based on CIP data; item not viewed.
Master record variable field(s) change: 072
Keywords: Catechetics -- History -- Early church, ca. 30-600.; Baptism -- History -- Early church, ca. 30-600.; Eschatology -- History of doctrines -- Early church, ca. 30-600.; Martyrdom -- Christianity -- History; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Baptism -- Early church; Catechetics -- Early church; Eschatology -- History of doctrines -- Early church; Martyrdom -- Christianity; Evangelistic work -- History -- Early church, ca. 30-600.; Religion; Worship -- History -- Early church, ca. 30-600.; RELIGION / Christian Church / History; 30-600; Electronic books; History